Administration of chiglitazar reverses chronic stress-induced depressive-like symptoms in mice via activation of hippocampal PPARα and BDNF - Zhou, Jiu-Jian; Zhao, Jie; Gao, Shang-Yan; Gao, Yuan-yuan; Chen, Cheng; Ding, Yi; Wu, Zhong-hua; Chen, Pu-Jian (Frontiers in Pharmacology, 2025)
BackgroundDeveloping non-monoamine based novel antidepressants is now popular and necessary. Peroxisome proliferator-activated receptor α (PPARα) has been demonstrated to play a role in the pathophysiology of depression, and several PPARα agonists including WY14643, fenofibrate, and gemfibrozil, have all been reported to possess antidepressant-like efficacy in rodents. Chiglitazar is a novel pan agonist of PPARs, and this study aims to investigate whether this agonist has beneficial effects against depression.MethodsChronic unpredictable mild stress (CUMS), chronic restraint stress (CRS), forced swim test (FST), tail suspension test (TST), sucrose preference test (SPT), western blotting, and adeno-associated virus (AAV)-mediated gene transfer were adopted together in the present study.ResultsIt was found that repeated intraperitoneal (i.p.) injection of chiglitazar significantly reversed both CUMS-induced and CRS-induced depressive-like behaviors in mice in the FST, TST, and SPT. Chiglitazar treatment also fully reversed both CUMS-induced and CRS-induced downregulation in the expression of hippocampal PPARα and brain-derived neurotrophic factor (BDNF) signaling in mice. Furthermore, pharmacological blockade of hippocampal PPARα and BDNF signaling attenuated the antidepressant-like effects of chiglitazar in mice. Genetic knockdown of hippocampal PPARα and BDNF also abolished the antidepressant-like actions of chiglitazar in mice.ConclusionIn summary, administration of chiglitazar reverses chronic stress-induced depressive-like symptoms in mice via activation of hippocampal PPARα and BDNF.